PERLINDUNGAN TERHADAP PENCIPTA APLIKASI CXM (STUDI PUTUSAN NOMOR 60/PDT.SUS-HAK CIPTA/2020) - Amelia Nofianti; Simona Bustani (Reformasi Hukum Trisakti, 2021)
Today companies find it difficult to maintain ownership of computer program copyrights. One of the copyright ownership cases for the CXM application was PT Telekomunikasi Indonesia with a programmer named Iman Fauzan Syarief where Iman claimed the application copyright belonged to him. The formulation of the problem is how is the legal protection for the creator of the CXM application which was previously registered in the name of Iman Fauzan Syarief based on the UUHC and what is the impact of recording the copyright of the CXM application on behalf of Iman Fauzan Syarief to PT Telkom based on UUHC. This research method uses normative research methods, is descriptive using secondary data and primary data, and draws conclusions by deductive method. The results of the research, discussion and conclusion are that the legal protection for the creator of the CXM Application is protected under Articles 33, 34, 35 and 37 UUHC and PT Telkom is declared the creator, and the recording of the CXM Application by programmer Iman Fauzan Syarief does not give birth to a copyright.